PP71 Cultures of Evidence Among Decision-Makers in Non-Health Fields: Systematic Review of Qualitative Evidence. (10th September 2013) - Lorenc, T; Tyner, E; Petticrew, M; Martineau, F; Phillips, G; Lock, K
Abstract : Background: Many non-health public policy sectors which form part of local government may have impacts on population health outcomes. Decision-makers' views about research evidence, and their practices of evidence use, are less well understood in these sectors than in healthcare or public health. Methods: Systematic review (PRISMA) of qualitative evidence. A range of sources were searched. Studies were included if: they included local policy-makers or practitioners in transport, housing, urban planning and regeneration, crime and policing, or licensing; and reported substantive data on views, beliefs or experiences regarding research evidence. Study findings were synthesised using a grounded-theory thematic analysis approach. Results: A range of contextual factors impact on evidence use, including personal contacts, institutional structures and power relationships, and national legal or policy constraints. Academic research evidence is often a relatively small part of the overall knowledge base for decision-making. The types of evidence used vary considerably across sectors: evaluations of effectiveness are generally a secondary concern, with descriptive evidence on contexts being more highly valued. General messages about the value of evidence-based policy and practice have been widely disseminated, and some sectors report relatively high rates of evidence use. However, decision-makers' understandings of these messages are highly divergent, and the ways evidence is used in practice often do not conform to academic researchers' preconceptions. Discussion: Compared to healthcare or public health, cultures of evidence in non-health sectors present distinct issues. The findings of this review indicate the need for a broader perspective on evidence use, which takes into account the whole decision-making process, and the interaction of academic research with more informal and situated forms of knowledge. Linear models of 'knowledge translation' may not capture the complexity of potential relations between knowledge and practice, and the wide variation in decision-makers' understandings of the concept of evidence.